UPAYA PEMERINTAH MALAYSIA DALAM MENCAPAI AGENDA MALAYSIAN VISION 2020â MELALUI KERJASAMA BILATERAL DENGAN AMERIKA SERIKAT - kurniawan, Ikhsan; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Malaysia is a country in Southeast Asia that has a rapid rate of economic progress. Since the late 1980s until the 2000s the rate of growth of Malaysias economy nearly tripled. This achievement did not escape capacity charismatic leader of Malaysia, Mahathir Mohammad who is has launched a program of Malaysia Vision 2020. Malaysian Vision 2020 is a policy that contains a variety of economic development strategies concepts in a systematic and planned figures declared by the founder (founding father) as a condition of rational and systematic Malaysia can bring progress toward better national development.This study used descriptive qualitative methodology, in which the collected data is non-numeric. While data collection techniques used are library research. Then the theory is used to answer the formulation / identification problem is constructivism theory elaborated by policy-making capacity which is then associated with the development of the theory negara.teori international cooperation, foreign policy are realized through cooperation with the United States governmentefforts / policies implemented by the Malaysian government in realizing the agenda of Malaysia Vision 2020 in collaboration with the U.S. government through the equation of understanding the vision of leaders of both countries are realized through the visit and tour of the state, is realized through the development of cooperation in the economic, political, social and cultural.Keyword : Political Economy and malaysia malaysian vision 2020